STRATEGI IBU SINGLE PARENT DALAM MEMENUHI KEHIDUPAN KELUARGA DI DESA BATAS KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU - Resta, Monica; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research contains the strategy of single parent mothers in fulfilling family life and the efforts made to overcome the problems faced in the Border Village, Tambusai District, Rokan Hulu Regency. This study aims to determine the problems faced by single parent mothers in living life without the presence of a partner and the efforts made to meet family needs. The research method used in this study was qualitative with six subjects who were single parent mothers with two or more dependents. The data collection technique used is in the form of observation, interviews and documentation that supports the validity of this research data. The results of field research show that the problems faced by single parent mothers in fulfilling family life are (1). Difficult economy with mediocre income because trying to work and looking for additional income (2). Single parents are required to make a living on their own and without the help of other parties (family) (3). Feeling lonely and losing a main economic support figure, makes you have to live a hard life. The conclusion of the study that: single parents are always underestimated by the surrounding community. The economic side they always feel squeezed by the economy. Due to being busy working, having to make a living, single parent mothers have limited time to care for children..